Extended spectrum beta-lactamase and fluoroquinolone resistance genes among Escherichia coli and Salmonella isolates from children with diarrhea, Burkina Faso - René Dembélé; Ali Konaté; Oumar Traoré; Wendpoulomdé A. D. Kaboré; Issiaka Soulama; Assèta Kagambèga; Alfred S. Traoré; Nathalie K. Guessennd; Awa Aidara-Kane; Amy Gassama-Sow; Nicolas Barro (BMC, 2020)
Abstract Background The emergence and spread of multidrug-resistant gram-negative bacteria (MDR) has become a major public health concern worldwide. This resistance is caused by enzymes-mediated genes (i.e., extended spectrum beta-lactamases) that are common in certain Enterobacterioceae species. However, the distribution of these genes is poorly documented in Burkina Faso. This study aims to determine the prevalence and distribution of the resistant genes coding for broad spectrum beta-lactamases and quinolones in rural Burkina Faso. Methods Multiplex PCR assays were carried out to detect ESBL-encoding genes, including bla OXA, bla TEM, bla CTX-M, bla SHV. The assays also assessed the presence of quinolone resistance gene namely qnrA, qnrB and qnrS in the quinolone-resistance DEC and Salmonella strains. Results The Extended-Spectrum Beta-Lactamases (ESBL) resistance phenotype was reported in all the E. coli isolates (5/5). Cross-resistance phenotype to quinolones (CRQ) was shown by one Salmonella strain (1/9) and three E. coli (3/5). Cross-resistance phenotypes to fluoroquinolones (CRFQ) were harboured by one Salmonella (1/9) and carbapenemase phenotypes were detected in two E. coli strains (2/5). Whilst the bla OXA genes were detected in 100% (5/5) of E. coli isolates and in 33.33% (3/9) Salmonella isolates. One strain of E. coli (1/5) harbored the bla CTX−M gene and the qnrB gene simultaneously. Conclusions This study identified β-lactam (bla) and quinolone resistance (qnr) genes in multidrug-resistant E. coli and Salmonella spp. in rural Burkina Faso. Our finding which highlighted the enterobacteriaceae strains resistance to β-lactams and quinolones are of high interest for adequate management of antimicrobial resistant genes outbreak in Burkina Faso.